A REVIEW ARTICLE: BACTERIAL PLASMIDS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
Plasmids are genetic elements of extra chromosomal double stranded, the replication of plasmids is independently of the genomic DNA. Plasmids are integrate with chromosome to form episomes, also they vary from chromosomes when they tiny and code for gene that is not basic to existence of bacteria. Loss of plasmid not slay bacteria, while the existence of plasmids give interest for bacteria. The Plasmid of bacteria differ if the lesser it involved 846bp so long as include single gene. Other plasmids has up 500 genes, while the greater carry 1,674 genes.